Meningioma em placa atingindo toda a convexidade cerebral "Meningioma en plaque" involving the entire cerebral convexity - M. de Almeida; Jamil Salum; Cleusa M. Mantovani; Marcelo Marcondes (Arquivos de Neuro-Psiquiatria)
É apresentado caso de extenso meningioma em placa atingindo toda a convexidade e determinando grande hiperostose da calota craniana. O quadro clínico caracterizou-se por aumento do volume do crânio, cefaléia, déficit de visão e convulsões. As radiografias e o estudo necroscópico mostraram que as tábuas ósseas foram substituídas por espículas dispostas radialmente. O aspecto histológico, típico de meningioma, não sugeria malignidade. The case of a patient with hystologically confirmed meningeoma is reported. The tumor extended continuously over the entire cerebral convexity and promoted remarkable hyperostosis of the skull. Headache, blindness, increased skul and convulsions were the main clinical manifestations. The two laminae of the skull were replaced by spikes radially arranged, as suggested by the X-ray picture and confirmed at necropsy. The hystologic aspect of the tumor did not show evidence of malignity.